Effleurage massage and sanyinjiao point acupressure on reducing dysmenorrhea - Afriani, Anita Indra; Listiani, Dwi; Mujahidah, Sa'adah; Mayangsari, Dewi; Adi Puteri, Vita Triani; Sulistiyowati, Dwi (CV LINK Education Publication, 2024)
Introduction: Dysmenorrhea, often known as menstrual discomfort, is one of the complications that might arise as a result of the menstrual cycle which adolescents experience. One of the many approaches that can be utilized to treat dysmenorrhea is a combination of effleurage massage and acupressure applied to the sanyinjiao point (SP 6). Objectives: To find out if effleurage massage and sanyinjiao point acupressure can help female students with primary dysmenorrhea was the point of this study. Methods: This investigation implemented a quasi-experimental methodology that included a control group and pre-and post-tests. Incidental sampling was implemented. The 26-person sample was divided into two groups: the first group received effleurage massage (n = 13), and the second group received acupressure at the sanyinjiao point (SP 6) (n = 13). The NRS was employed to evaluate dysmenorrhoea pain, and the paired T-test and Mann-Whitney tests were implemented. Results: The findings indicated a significant difference in the degree of primary dysmenorrhea discomfort before and after the effleurage massage intervention among female students p-value of 0.000. A significant difference exists in the intensity of primary dysmenorrhea pain before and after acupressure at the sanyinjiao point (SP 6) among female students p-value of 0.000. Conclusion: Effleurage massage and acupressure at the sanyinjiao point (SP 6) effectively alleviate dysmenorrhea discomfort with a p-value of 0.017.